COMPARISON OF CREEP OF BRAZILIAN SELF COMPACTING CONCRETE WITH DIFFERENT PREDICTION MODELS - Marques, Ana C.; Kataoka, Luciana T.; Machado, Marcelo A. S.; Barbosa, Monica P. [UNESP]; Bittencourt, Tulio N.; Shi, C. J.; Yu, Z. W.; Khayat, K. H.; Yan, P. Y. (R I L E M Publications, 2009)
Self compacting concrete (SCC) is a composite that was recently developed in Japan in the early 1990's. In Brazil, the studies with SCC started at the early 2000's. SCC offers several advantages as compared to the ordinary concrete. In Brazil, the construction industry is starting to introduce SCC in the market and there is no standard code for this material. Since it is a recent material there is also no study related to both short term and long term behaviors of Brazilian SCC. In order to contribute to this field, this paper publishes the first results of creep tests with SCC performed in Brazil. This paper also shows the comparisons of SCC results to the results from the American, the European, and the Brazilian prediction models.
Keywords: creep; prediction models; Brazilian concrete